Internal security services in liberalizing states transitions, turmoil, and (in)security - Derdzinski, Joseph L. (Ashgate Pub., 2009)
Discusses the importance of incorporating major institutional actors in the course of political liberalization. This book focuses on democracy and its non-democratic institutions in an era of stalled liberalization. It presents a comparative account of internal security situations of Morocco and Indonesia.